Phosphate fertilization on nutritional status and growth of upland rice cultivars - Crusciol, C. A.C. [UNESP] (2019)
Differences among rice genotypes demonstrate that root system of upland rice cultivars influences P acquisition and growth performance. We studied root and shoot growth and nutrition of traditional and modern cultivars of upland rice as affected by P availability (three rates). At the highest P rate, the greatest dry mass was obtained with Maravilha, which was on average 180% higher than Caiapo. The modern has exceeded the traditional in growth performance, besides accumulating more nutrients. Maravilha was more efficient in root and shoot growth, and nutrient absorption with P supply, using less photoassimilates for root growth. Traditional cultivars of upland rice may develop better than modern cultivars in low P availability, with facilitates its adaptation in soils with this condition. Modern cultivars are more responsive to P fertilization, which demonstrates a better option in a cropping system with P supply to aim at high yield.